2019
DOI: 10.12659/msm.913674
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Compressive Force Induces Differentiation of Osteoclasts with High Levels of Inorganic Dissolution

Abstract: Background Osteoclast precursor cells are constitutively differentiated into mature osteoclasts on bone tissues. We previously reported that the continuous stimulation of RAW264.7 precursor cells with compressive force induces the formation of multinucleated giant cells via receptor activator of nuclear factor κB (RANK)-RANK ligand (RANKL) signaling. Here, we examined the bone resorptive function of multinucleated osteoclasts induced by continuous compressive force. Material/Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In vitro studies of osteoclast precursor cells have shown that continuous compressive force positively affects osteclastogenesis. 16,17 In contrast, the application of tensile force to preosteoclasts stimulated with RANKL decreased the number of osteoclasts. 18 In terms of vibratory stimuli, treatment of preosteoclast cells with 0.3 g at 45 Hz for 15 min/d significantly decreased the number of RANKL-induced TRAP-positive multinucleated cells (MNCs) and inhibited osteoclast formation.…”
Section: Introductionmentioning
confidence: 98%
“…In vitro studies of osteoclast precursor cells have shown that continuous compressive force positively affects osteclastogenesis. 16,17 In contrast, the application of tensile force to preosteoclasts stimulated with RANKL decreased the number of osteoclasts. 18 In terms of vibratory stimuli, treatment of preosteoclast cells with 0.3 g at 45 Hz for 15 min/d significantly decreased the number of RANKL-induced TRAP-positive multinucleated cells (MNCs) and inhibited osteoclast formation.…”
Section: Introductionmentioning
confidence: 98%
“…In vitro studies have demonstrated the induction of osteoclast differentiation in response to generation of various types of compressive force, varied cellular responses have been observed in these models. 8 , 9 , 10 , 11 , 12 Weight loading is simple for mechanical loading model but physical cell damage and nutrient restriction from direct contact between weight-generating materials and cells are limitations. In order to prevent direct contact and assure the constant force distribution on the cell culture, an air-pump compressor to create air pressure is suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Another study exert force by increasing the amount of culture medium to osteoclast precursor cells. 9 It is possible that the increased of nutrients in the environments. In this study, to address the limitations of existing models of compressive force, we developed a novel hydrostatic pressure-generated compressive model based on pestles and cylinders.…”
Section: Introductionmentioning
confidence: 99%
“… 9 The mechanosensitive nature of bone cells and the stimulating effects of matrix stiffness on osteoblasts, osteocytes, and chondrocytes have been extensively studied. 10 , 11 , 12 Although osteoclast differentiation has been proven to be influenced by multiple mechanical stimuli, such as tension force, 13 microgravity, 14 fluid shear stress, 15 vibration, 16 and compressive forces, 17 the activity of osteoclasts in response to different degrees of microenvironmental stiffness remains unclear.…”
Section: Introductionmentioning
confidence: 99%